COVID-19 Pandemic Response in a Migrant Farmworker Community: Excess Mortality, Testing Access and Contact Tracing in Immokalee, Florida. Issue 1 (7th September 2022) - Limaye, Neha; Ninesling, Brennan; Marcelin, Frantzso; Nolan, Cody; Sobba, Walter; Hing, Matthew; Ptaszek, Emily; Léandre, Fernet; Palazuelos, Daniel
Background: Migrant and seasonal farmworkers face enormous barriers to health and have been a particularly vulnerable population during the COVID-19 pandemic, but their pandemic experiences and potential inequities have not been well studied. Objectives: We aimed to assess the impact of COVID-19 in Immokalee, Florida, a community with a significant population of migrant and seasonal farmworkers. We evaluated for differences in pandemic experience by language, a known barrier to healthcare, to inform and strengthen future public health efforts. Methods: First, to estimate the burden of COVID in the area, we conducted a descriptive analysis of data on COVID-19 deaths for Collier County from May-August 2020. We then surveyed a cross-sectional, randomized representative sample of 318 adults living in Immokalee from March-November 2020 to assess socio-demographics, workplace conditions, sources of information, ability to follow guidelines, and experiences with testing and contact tracing programs. Results were compared across language groups. Findings: Average excess mortality in Collier County was 108%. The majority surveyed in Immokalee had socio-demographic factors associated with higher COVID risk. Non-English speakers had higher workplace risk due to less ability to work from home. Haitian Creole speakers were less likely to be tested, though all participants were willing to get symptomatic testing and quarantine. Those participants who tested positive or had COVID-19 exposures had low engagement with the contact tracing program, and Spanish-speakers reported lower quality of contact tracing than English speakers. Conclusions: The community of Immokalee, FL is a vulnerable population that suffered disproportionate deaths from COVID-19. This study reveals language inequities in COVID testing and contact tracing that should be targeted in future pandemic response in Immokalee and other migrant farmworker communities.